Menerjemahkan Perubahan Dari TCL (Teacher Center Learning) Ke SCL (Student Center Learning) - I Ketut Muliarta (Jayapangus Press, 2018)
The problematic education in Indonesia still uses the old paradigm, which is dominated by the role and activities of teachers. In answer the problematic of the National Education System Law No. 20 of 2003 indicates a change from teaching to learning. The rationale above becomes imperative of teachers should have insight into the characteristics of student-centered learning so that it can be applied in learning. Student-centered learning encourages students to be actively involved in building knowledge, attitudes and behaviors. In the student-centered learning process, students have the opportunity and facilities to build their own knowledge so that they will gain a deep understanding and ultimately improve the quality of the students. Innovative learning with student-centered methods has a diversity of learning models / methods that demand the active participation of students. There are several SCL (1) Small Group Discussion (SGD) learning models (2) Role-Play and Simulation. (8) Collaborative Learning (CbL) (9) Project Based Learning (PBL) ). It is expected that educators will make this learning model (Student Centered Learning) as an alternative in the learning process.